Chronic genital ulcer in a teenager reveals orificial cutaneous tuberculosis. - Riswanto, C.D.; Widia, Y.; Sawitri, S. (European Journal of Pediatric Dermatology, 2026)
Tuberculosis cutis orificialis (TCO) is a rare form of cutaneous tuberculosis, accounting for approximately 2% of cases and typically involving the oral cavity, external genitalia, endometrium, or anal region. Despite its rarity, TCO presents significant diagnostic challenges due to its heterogeneous clinical and histopathological features. A case of genital ulceration in a 15-year-old boy was diagnosed as TCO through the GeneXpert integrated system. This case highlights the diagnostic complexity of TCO, particularly when routine tests and histopathology yield nonspecific findings. TCO should be considered in the differential diagnosis of chronic genital ulcers, especially in tuberculosis-endemic regions, to ensure timely and effective treatment.